Allan-Herndon-Dudley-Syndrome: Considerations about the Brain Phenotype with Implications for Treatment Strategies - Krude, Heiko; Biebermann, Heike; Schuelke, Markus; Müller, Timo D.; Tschöp, Matthias (Experimental and Clinical Endocrinology & Diabetes, 2020)
Despite its first description more than 75 years ago, effective treatment for “Allan-Herndon-Dudley-Syndrome (AHDS)”, an X-linked thyroid hormone transporter defect, is unavailable. Mutations in the SLC16A2 gene have been discovered to be causative for AHDS in 2004, but a comprehensive understanding of the function of the encoded protein, monocarboxylate transporter 8 (MCT8), is incomplete. Patients with AHDS suffer from neurodevelopmental delay, as well as extrapyramidal (dystonia, chorea, athetosis), pyramidal (spasticity), and cerebellar symptoms (ataxia). This suggests an affection of the pyramidal tracts, basal ganglia, and cerebellum, most likely already during fetal brain development. The function of other brain areas relevant for mood, behavior, and vigilance seems to be intact. An optimal treatment strategy should thus aim to deliver T3 to these relevant structures at the correct time points during development. A potential therapeutic strategy meeting these needs might be the delivery of T3 via a “Trojan horse mechanism” by which T3 is delivered into target cells by a thyroid hormone transporter independent T3 internalization.
Keywords: Thyroid hormone transporter; Allan-Herndon-Dudley-Syndrome; pathophysiology